ETHICS AND MANAGEMENT ISSUES IN EDUCATION - Major Sakiyev Sardor Shukhratovich (American Journals Publishing, 2024)
This article explores the intersection of ethics and management in the educational sector, focusing on the challenges and considerations that arise in promoting equitable, transparent, and effective practices. It examines the principles of ethical leadership, resource allocation, and stakeholder relationships while addressing conflicts such as discrimination, inequity, and corruption. The discussion highlights strategies for fostering ethical cultures within educational institutions and ensuring that management decisions align with moral and professional standards. The findings underscore the importance of integrating ethics into management frameworks to achieve sustainable and inclusive educational outcomes.
Keywords: Ethics in education, educational management, leadership, equitable practices, resource allocation, corruption, ethical decision-making, transparency.